1985
DOI: 10.1056/nejm198511213132104
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Complications Associated with the Lupus Anticoagulant

Abstract: We identified eight patients with the lupus anticoagulant (an autoantibody acquired by some patients with systemic lupus erythematosus), by observation of an increased activated partial thromboplastin time and abnormal results on a tissue thromboplastin-inhibition test. The patients had experienced a total of 30 spontaneous abortions and fetal deaths in 31 previous pregnancies (96.8 per cent). During their next pregnancy, the patients were treated with 40 to 50 mg of prednisone per day and 81 mg of aspirin per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
1
14

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(164 citation statements)
references
References 41 publications
4
145
1
14
Order By: Relevance
“…This is the first prospective controlled study to examine the frequency of subclinical lupus, anti-Ro, LAC, and ACL antibodies in women who were habitual aborters. Previous reports have included women who did not meet the standard definition of habitual abortion (3 or more consecutive spontaneous abortions) (8,10,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first prospective controlled study to examine the frequency of subclinical lupus, anti-Ro, LAC, and ACL antibodies in women who were habitual aborters. Previous reports have included women who did not meet the standard definition of habitual abortion (3 or more consecutive spontaneous abortions) (8,10,20).…”
Section: Discussionmentioning
confidence: 99%
“…The LAC may play a role in fetal loss through uteroplacental thrombosis (26). The impression is given in the literature that there is a clearly established relationship between antiphospholipid antibodies and recurrent abortions, and furthermore, that treatment may lead to successful pregnancy, whereas lack of treatment almost uniformly results in unsuccessful pregnancy (3,7,8,17). Series of lupus patients with antiphospholipid antibodies and recurrent abortions have been described (3,4,7,15), but a similarly strong association between LAC and recurrent abortion has been believed to exist in women without clinical lupus To ensure detection of relevant antiphospholipid antibodies, we employed 3 assays, APTT, RVVT (a coagulation assay for LAC), and ACL, in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in early-onset severe preeclampsia most studies found an association with positive tests for aCL, testing in these patients may have therapeutic implications for future pregnancies. Women with APS are also at a substantial risk for IUGR [40,51,53] which is around 30%. In one study, 24% of mothers delivered of IUGR infants had medium or high positive tests for aCL [54].…”
Section: Aquired Thrombophiliamentioning
confidence: 99%
“…Women with SLE and aPL have a rate of fetal death up to six times higher when compared with healthy women (27,28). Moreover, among women with high levels of aPL, a history of prior fetal losses appears to compound the risk for further fetal demise.…”
Section: Recurrent Spontaneous Abortionmentioning
confidence: 99%